Desain Model Pengelolaan Kebun Kelapa Sawit Plasma Berkelanjutan Berbasis Pendekatan Sistem Dinamis (Studi Kasus Kebun Kelapa Sawit Plasma PTP Nusantara V Sei Pagar, Kabupaten Kampar, Provinsi Riau) - I Gusti Putu Wigena; Hermanto Siregar; nFN Sudradjat; Santun R.P. Sitorus (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2009)
EnglishManagement of nucleus smallholder oil palm after the conversion is not meeting the recommendation standard which leads to the production decrease. For this reason, this research was conducted at PTP Nusantara V Sei Pagar nucleus smallholder oil palm, Kampar District, Riau Province from January 2007 to March 2008. The objectives of this research are to design sustainable management model of nucleus smallholder oil palm meet the biophysical (planet), economical (profit) and social (people) aspects. The research extensively used primary and secondary data of biophysical, economical and social aspects. Sources of the biophysical secondary data were PTPN V and related local government institutions. The biophysical primary data was collected through observation method, while economical and social data were collected through interview technique with farmers, farmer’s groups and Village Cooperative Unit staffs using structured questionnaires. There were 100 respondents, selected randomly using stratified random sampling method. The data was analyzed using Power Sim program. The results showed that the design of sustainable nucleus smallholder oil palm management model for 2010-2035 satisfies biophysical, economical and social aspects. The indicators namely fresh fruit bunch yield at about 25.83 ton/ha/year, the increasing of soil degradation and the decreasing of environmental capacity at lower levels of about 0.03-0.8% and 0.002-0.1%, respectively. The average farmer’s income at Rp. 22,859,950/ha/year, and community income surrounding the oil palm plantation at the average of Rp. 16,845,025/year, a value that higher than the regional minimum wage of Riau Province. Human resources quality increased indicated by the education level equivalent with the income of oil palm labor at about Rp. 55 million annually.IndonesianPengelolaan kebun kelapa sawit plasma pascakonversi tidak sesuai standar yang dianjurkan sehingga berdampak terhadap penurunan produksi. Untuk itu, telah dilakukan penelitian di kebun kelapa sawit plasma PTP Nusantara V Sei Pagar, Kabupaten Kampar, Provinsi Riau dari bulan Januari 2007 sampai Maret 2008. Tujuan penelitian adalah untuk merancang model pengelolaan kebun kelapa sawit plasma berkelanjutan yang memenuhi aspek biofisik (planet), ekonomi (profit), dan sosial (people). Penelitian menggunakan data primer dan sekunder yang menyangkut aspek biofisik, ekonomi, dan sosial. Data sekunder bersumber dari PTPN V dan instansi terkait pemerintah Daerah Provinsi Riau. Data primer biofisik dikumpulkan dangan observasi lapang, data ekonomi dan sosial dikumpulkan melalui wawancara langsung ke petani, kelompok tani dan staf KUD dengan kuesioner terstruktur. Jumlah responden sebanyak 100 orang yang diambil secara acak bertingkat (stratified random). Data terkumpul dianalisis dengan program Power Sim. Hasil penelitian menunjukkan bahwa model pengelolaan berkelanjutan yang dirancang untuk periode 2010-2035 mampu memenuhi aspek biofisik, ekonomi, dan sosial dengan indikator produksi tandan buah segar (TBS) rata-rata 25,83 ton/ha/tahun, peningkatan degradasi lahan dan penurunan daya dukung lingkungan sangat rendah, masing-masing sebasar 0,03-0,08 persen dan 0,002-0,01 persen. Pendapatan petani rata-rata sebesar Rp 22.859.950/ha/tahun dan pendapatan masyarakat sekitar kebun rata-rata Rp 16.845.025/tahun yang melebihi tingkat Upah Minimum Regional Provinsi Riau. Kualitas sumberdaya manusia meningkat yang tercermin dari tingkat pendidikan yang disetarakan dengan pendapatan yang diperoleh sebagai tenaga kerja di perkebunan kelapa sawit sampai Rp 55.000.000/tahun.